A new As3Mo8V4/PANi/rGO composite for high performance supercapacitor electrode. Issue 15 (1st August 2021) - Song, Yao; Su, Zhanhua; Zhao, Zhifeng; Lin, Shuangyan; Wang, Dan
Abstract: Herein, [As2 III As V Mo8 VI V4 IV O40 ]2 [Cu I Cu2 II (pz)4 ]2 ·9H2 O/polyaniline/reduced graphene oxide (pz = pyrazine, abbreviated to As3 Mo8 V4 /PANi/rGO) composite is first assembled, characterized and systematically explored for its supercapacitor performance. As3 Mo8 V4 /PANi/rGO composite shows a exceptional specific capacitance (2351 F g −1 at 1 A g −1 ) and outstanding cyclic stability (96.9% after 5000 cycles). The symmetric supercapacitor exhibits high specific capacitance of 1295 F g −1 at 1 A g −1 and excellent energy density of 88.1 Wh kg -1 at power density of 349.6 W kg -1, while maintaining a notable capacitance retention of 85.7% after 5000 cycles at 2 A g -1 . The above results confirm the potential application of As3 Mo8 V4 /PANi/rGO composite in energy storage devices. Graphical abstract: Image 1 Highlights: The As3 Mo8 V4 /PANi/rGO composite is assembled by ultrasonic method. The composite has high specific capacitance. The composite shows outstanding cycling stability.